Pacific media councils and cultural values: Safety valve or entrenched hegemony? - David Robie (Asia Pacific Network, 2003)
Two countries in the South Pacific, Fiji and Papua New Guinea, have adopted contrasting media council models to self-regulate the media amid growing political and cultural pressures on the news industry. Projected as promoting media standards  and professionalism and a model for the region, the realities have raised questions about whether such bodies are self-regulatory mechanisims genuinely working in the public interst in the Pacific or defending entrenched media and power relationships, some foreign, from pressure by island governments, There are also questions over whether codes of ethics promoted by the council are effective as self-regulatory tools for the media. Exploring case studies such as media coverage of the controversial John Scott double murder case in Fiji, the Speight attempted coup and political crisis in Papua New Guinea, this article exammines thses dilemmas and also whether codes of practice reflect regional 'Pacific way' cutlural values, or are in fact adopted as part of globalisation.